2018
DOI: 10.28991/cej-0309171
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study to Investigate the Efficiency of Steel and Polypropylene Fiber in Enhancing the Durability Properties of Concrete Composites

Abstract: Concrete deterioration is associated with factors like surface abrasion and transport of water through capillary action in the concrete matrix. These factors may catalyse other forms of deformation such as cracking and corrosion of reinforcing steel. This paper presents an experimental evaluation to compare the effectiveness of steel and polypropylene fiber in enhancing the mechanical and durability properties, in terms of impact, sorptivity, and abrasion. In the present study, abrasion resistance is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The rate of decrease in slump value of crimped SF was approximately twice as compared to PPF of the same percentage. Most of the results presented in Table 3 are already reported in the literature 44 . From Table 3 it can be seen that the percentage decrease in a slump was approximately 30% for PFRC mixes having 0.5% PPF by volume of concrete.…”
Section: Resultsmentioning
confidence: 59%
“…The rate of decrease in slump value of crimped SF was approximately twice as compared to PPF of the same percentage. Most of the results presented in Table 3 are already reported in the literature 44 . From Table 3 it can be seen that the percentage decrease in a slump was approximately 30% for PFRC mixes having 0.5% PPF by volume of concrete.…”
Section: Resultsmentioning
confidence: 59%
“…The PPF ratio augmentation lessened minimally the electrical resistivity [6,9] and for concrete having silica fume and fly ash diminished the dry shrinkage and carbonation depth but somewhat increase the freeze-thaw resistance [10]. An influential reduction in capillary porosity obtained by sorptivity test via utilizing PPF in concrete and this has a good impact on the reinforced concrete structures durability, besides, a linear trend with strong correlation was obtained between PPF volume fraction and initial sorptivity median, also, it was mentioned that PPF enhanced concrete surface abrasion remarkably [28]. The compressive strengths versus their PPF ratios of several studies are shown in Fig.…”
Section: Normal and High Strength Concrete With Ppfmentioning
confidence: 96%
“…Comparing with steel arch bridge and concrete filled steel tube arch bridge, the cost of concrete arch bridge with the same span is the lowest. In the past 20 years, the span of concrete arch bridge has been increasing rapidly and great progress has been achieved all over the world [2][3][4][5][6][7][8]. Among them, a series of researches on super long span concrete arch bridge were first conducted in Japan and Croatia [9].…”
Section: Introductionmentioning
confidence: 99%